Isolation and anti-Xanthomonas citri activity of unguinol produced by Aspergillus unguis CBMAI 2140 - dos Santos, Eduarda Araujo [UNESP]; Marin, Vítor Rodrigues [UNESP]; de Angelis, Derlene Atilli; Ferreira, Henrique [UNESP]; Sass, Daiane Cristina [UNESP] (Oxford University Press (OUP), 2025)
This research investigated active biomolecules from the endophytic fungus Aspergillus unguis (CBMAI 2140), isolated from Passiflora incarnata leaves, as potential antibacterial agents against Xanthomonas citri subsp.citri, the causative agent of citrus canker. The fungal extract was obtained via liquid–liquid extraction with ethyl acetate. Antibacterial activity was assessed using the Resazurin Microtiter Assay Plate, determining inhibitory concentrations (IC90) and the minimum bactericidal concentration (MBC). The extract displayed microbicidal activity at 1050 µg ml−1 and inhibited bacterial growth at 350 µg ml−1. Fractionation of the extract via normal-phase column chromatography yielded six fractions, with fraction F11 showing the highest antibacterial potential (MBC: 200 µg ml−1). Nuclear magnetic resonance analysis identified Unguinol as the main compound in F11. Fluorescence microscopy demonstrated rapid permeabilization of the X. citri cell membrane upon exposure to the compound, with significant effects observed after 15–30 min. Although no notable anti-biofilm activity was detected, this study represents the first report of Unguinol’s antibacterial activity against Xanthomonas species. These findings highlight its potential for agricultural applications, contributing to sustainable development goal 2.
Keywords: antimicrobials; bacteria; biotechnology; fungi; plant disease control